'Red Flags of Corruption' in World Bank Projects An Analysis of Infrastructure Contracts - Kenny, Charles (The World Bank, 2010)
"Red flags" are indicators of potential issues regarding governance failure, collusion or corruption in projects. While some specific red flags can be powerful indicators of issues to be addressed, the hypothesis of this paper is that many proposed red flags are potentially too ubiquitous and randomly distributed to be useful as indicators of significant governance failure. The paper examines project documentation from a small sample of World Bank water and sanitation projects in an attempt to collect data on the presence or absence of 13 commonly accepted red flags. This paper finds that: (i) almost every contract reviewed raised at least one of 13 red flags analyzed; (ii) potentially tainted contracts did not exhibit notably more red flags than control contracts; and (iii) the occurrence of multiple red flags in the same contract was rare enough to suggest that joint occurrence was largely by chance, not as a result of a strongly causal inter-relationship between flags. The ubiquity and apparent randomness of these red flags suggests that their roll-out as a monitoring tool requires additional thought as to interpretation, context and use. The paper examines an alternate tool for uncovering potential problem projects - supplier concentration. Across a very small sample, there does appear to be a relationship between such concentration and potential problem projects